Modelization of the thermal coupling between the ITER TF coil conductor and the structure cooling circuit. (December 2016) - Gauthier, F.; Bessette, D.; Hoa, C.; Rousset, B.; Lacroix, B.
Abstract: The ITER Toroidal Field (TF) coils are required not to quench during the most demanding event: a plasma disruption followed by a fast discharge of the Central Solenoid (CS), the Poloidal Field (PF) coils and the Correction Coils (CC). This event creates large heat deposition in the ITER magnet stainless steel structures in addition to the conductor AC losses. In order to prevent quench occurring in the TF conductor, cooling channels, implemented in the TF coil structure (TFCS), have to remove a large fraction of the heat deposited. The first integrated TF and structure mock-up has been manufactured and then tested in the HELIOS cryogenic test facility (CEA Grenoble) to determine the thermal coupling between the TFCS and the TF conductor, both actively cooled by supercritical helium at 4.4 K and 5 bar. It consists in a stainless steel casing, a cooling pipe glued with resin in the casing groove, winding pack (WP) ground insulation, a radial plate and a copper dummy cable-in-conduit-conductor (CICC). Steady state as well as transient thermal characterizations have been completed in May 2015. Simulation results by thermal hydraulic codes (VENECIA/SuperMagnet) and some of the experimental data are presented and discussed. The thermal coupling between the helium in the cooling tube and the TF coil structure is then modelled as an equivalent heat transfer coefficient in order to simplify the thermal hydraulic (TH) models. Comparison between simplified coupling and detailed coupling is presented.